Mapping Indoor and Outdoor Environmental Radiation Exposure at a Nigerian Tertiary Institution: Evidence from Federal College of Education, Gombe, Gombe State. Nigeria - Muhammad Nuruddeen Abdulkareem; Isa Sabo Muhammad; Ibrahim Olanrewaju Abiodun; Muhammad Mudassir Usman; Mohammad Abubakar; Abdullahi Muhammad; Ahmad Alhassan; Mohammed Shettima Nur (Health Physics, 2026)
Natural background ionizing radiation from terrestrial and cosmic sources results in continuous exposure of the population, particularly in educational environments where staff and students spend prolonged periods indoors and outdoors. Monitoring ambient gamma radiation and associated health risks is therefore essential for ensuring radiological safety and regulatory compliance. This study assesses background gamma radiation levels and corresponding radiological risk indices within the Federal College of Education (Technical), Gombe, Gombe State, Nigeria. Indoor and outdoor ambient gamma dose rates were measured at selected campus locations using a calibrated Radiation Alert Inspector Geiger–Muller detector. Measurements were conducted at a height of 1 m above ground level in accordance with UNSCEAR guidelines, with geographic coordinates recorded using a GPS receiver. Absorbed dose rate (ADR), annual effective dose equivalent (AEDE), and excess lifetime cancer risk (ELCR) were calculated using standard conversion factors and appropriate occupancy coefficients. Descriptive statistics were applied to evaluate spatial variability and compare results with international recommended reference levels. Indoor absorbed dose rates ranged from 15.00 to 46.67 nGy h −1 , while outdoor values ranged from 15.00 to 40.00 nGy h −1 . The mean indoor AEDE (0.227 mSv y −1 ) was higher than the outdoor mean (0.049 mSv y −1 ), primarily due to differences in occupancy factors. All estimated AEDE and ELCR values remained below the ICRP-recommended reference level of 1 mSv y −1 for public exposure, with spatial analysis revealing localized variability but no abnormal radiation hotspots. The findings indicate that ambient gamma radiation levels within the campus are within global background ranges and pose no significant radiological health risk. Regular monitoring is recommended to ensure sustained radiological safety in educational environments.